Martin Bucer's Doctrine of Justification: Reformation Theology and Early Modern Irenicism. - Klauber, Martin I. (Fides et historia, 2013)
The article reviews the book "Martin Bucer's Doctrine of Justification: Reformation Theology and Early Modern Irenicism," by Brian Lugioyo.